DINÂMICA E DISTRIBUIÇÃO DE METAIS NO COMPLEXO ESTUARINO ARRAIAL/ SÃO JOSÉ, MARANHÃO. - AZEVEDO, Igor Hamid Ribeiro (2019)
Estuaries are ecologically important environments, playing a fundamental role in the cycling of nutrients, metals and organic compounds. However, the intense use of drainage basins has reduced the quality of the biogeochemical compartment, especially sediment. In this context, the Arraial/São José Estuarine Complex (ASJEC), a macrotidal estuary located at the Amazon-Semi-Arid interface, with the rivers Itapecuru, Munim, Tibiri and Paciência flowing into it. The aim of the present study was to determine the concentrations of metals (Al, Fe, Mn, Cu, Zn, Cr,Pb and Ni) in the bottom sediment, identifying the main geochemical carriers of the metals according to the climatic variation characteristic of the region (rainy season and dry season). Sampling campaigns occurred in April (rainy season) and October (dry season) in 2017, with a total of 29 sampling points. Physico-chemical parameters such as temperature, salinity, dissolved oxygen, pH and suspended particulate matter were determined on the surface and at the bottom of the water column. The bottom sediment sampling for percentage of organic matter (OM), grain size and metals was carried out with the aid of a Gibbs dredge. The metals in the sediment were measured in the fraction <0.63 μm by flame atomic absorption spectrometry (FAAS) using partial extraction (50% Aqua-regia). The hydrochemical parameters varied according to the hydrological cycle of the region, influenced by the fluvial discharge during the rainy season and the action of the tides in the dry season. The sandy fraction was the most representative (> 85%) for both periods, with the grain size increasing toward the downstream estuary. It was observed low concentrations of OM, and retention upstream the ASJEC. The concentrations of metals were higher during the rainy season, upstream and near the rivers located in the São Luís Metropolitan Region (SLMR). The highest upstream values are related to the region similar to the Estuarine Turbidity Maximum (ETM) and the hydraulic barrier(HB). Statistical correlation showed that Al, Fe, Mn and MO oxyhydroxides were the main geochemical carriers. The Enrichment Factor (EF) estimated low anomalous levels for metals, indicating natural contributions to the environment. However, the Pb showed anomalous values and may be the result of the mineralogical composition of the local geology or anthropogenic contribution.